Hide and seek. Aspects of the dynamics of Bible translation - C. Lombaard (Acta Theologica)
Art may be viewed as fetish, in that it forces meaning on a chaotic world — a dynamic which is briefly illustrated in this article by means of Pablo Picasso’s famous painting, Les Demoiselles d’Avignon. Similarly, translations of the biblical texts, which result from very complex processes, may be viewed as fetishes. Translation thus requires a process of deducing and reducing meaning from relative chaos. A proper view of the nature of the Bible text and the theoretical load of exegetical and translation activities must be cultivated among lay translation users, particularly in our age of rising fundamentalisms. To this end, five suggestions are offered. This view affords Bible translators a more balanced status, namely one of humanity with dignity, than is at times found in some popular circles which regard Bible translators with severe suspicion.